Using the METRICS model for defining routes to scholarship in healthcare simulation. (3rd July 2018) - Cheng, Adam; Calhoun, Aaron; Topps, David; Adler, Mark D.; Ellaway, Rachel
Abstract: Introduction: In this paper, we explored the utility and value of the METRICS model for modeling scholarship in healthcare simulation by: (1) describing the distribution of articles in four healthcare simulation journals across the seven areas of METRICS scholarship; and (2) appraising patterns of scholarship expressed in three programs of simulation scholarship and reflecting on how these patterns potentially influence the pursuit of future scholarly activities. Methods: Two raters reviewed abstracts of papers published between January 2015 and August 2017 in four healthcare simulation journals and coded them using METRICS. Descriptive statistics were calculated for scholarship type and distribution across journals. Twenty-eight articles from three scholars were reviewed, with patterns of scholarship within articles mapped to METRICS. Descriptive synthesis was constructed through discussion between two reviewers. Results: A total of 432 articles from four journals were reviewed. The three most commonly published areas of scholarship were: 32.2% (139/432) evaluation, 18.8% (81/432) innovation, and 15.3% (66/432) conceptual. The METRICS model was able to represent different kinds of scholarship expressed in all of the papers reviewed and across programs of research. Reflecting on patterns of scholarship within their scholarly programs was helpful for research in planning future directions. Conclusions: The METRICS model for scholarship can describe a wide range of patterns of simulation scholarship within individual articles, programs of research, or across journals.